Relation between Social Responsibility and Enterprise Long-term Competitiveness - Zhang, Yongkui (International Journal of Emerging Technologies in Learning (iJET), 2013)
The theory of corporate social responsibility holds that a company must not only fulfill its economic responsibility of making profits for its shareholders, but also undertake broad legal, ethical and philanthropic responsibilities. The notion of corporate social responsibility is most vulnerable to the argument that fulfillment of social responsibility will affect the companyâ??s financial performance and competitiveness, which will in turn undermine the efficiency of the economy at large. To find an answer to this question, this paper draws upon the logical core of the stakeholder theory to design a framework for analyzing social responsibility and enterprise long-term competitiveness. This framework is then used to examine the Mengniu case, and the results show that fulfillment of social responsibility is a fountain of enterprise long-term competitiveness, fulfillment of social responsibility may reduce short-term financial performance somehow, but it will greatly increase long-term financial performance and enterprise long-term competitiveness.